Building Green Organizational Citizenship Behavior in the Electronics Industry: The Role of Green Transformational Leadership, Green Organization Culture and Green HRM - Erni Yuningsih; Ismartaya Ismartaya; Sri Harini; Cahya Sumirat (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The current phenomenon requires companies to adopt green organizational culture and transformational leadership as crucial strategies to foster green organizational citizenship behavior among employees. This study explores employee awareness of green organizational citizenship behavior influenced by Green Organizational Culture, Green Transformational Leadership, and Green Human Resources Management. The method used in data collection uses quantitative purposive sampling. There were 150 respondents from four divisions in a company engaged in the electronics sector. Data analysis used the SEM method with PLS 4 software. The study results concluded that GOC and GTL positively and significantly affect GHRM. GOC, GTL, and GHRM positively and significantly affect G-OCB. GHRM mediates GOC and GTL with G-OCB. The implication is that companies must invest resources in developing and implementing comprehensive GHRM practices.   Keywords: Green Organizational Culture, Green Transformational Leadership, Green Human Resources Management, Green Organizational Citizenship Behavior.